100 years of insulin: how the discovery of the hormone revolutionized the treatment of type 1 diabetes (Research, Society and Development, 2021)
The year of 2021 was a milestone for medicine and especially for patients diagnosed with diabetes, as it completed 100 years of the discovery of exogenous insulin. This medicine has completely revolutionized thousands of people's quality of life, as well as providing healthcare and the pharmaceutical industry a new perspective. In this context, it is important to show that type 1 diabetes mellitus is an autoimmune disease, meaning that the body itself attacks insulin-producing cells, called beta cells, therefore, it is essential that these patients use this hormone exogenously throughout their entire life's period. Currently, there are several types of insulin and technologies in constant development that aim to facilitate adherence and promote greater well-being for these people. Considering that the present literary review aims to describe the main types of diabetes, possible causes, existing treatments, consequences of lack of glucose control, the discovery of insulin, technologies and a brief comparison between the United States' and the Brazilian healthcare system. Using bibliographic materials as a research source, this article is a descriptive article about type 1 diabetes, which, considering the estimates and current prevalence, makes the discussion about this disease indispensable.